(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2024)
Despite the widespread use of multiple-choice (MC) tests in language teaching and the recognized importance of grammar instruction in language acquisition and assessment, there remains a dearth of research examining the suitability of MC tests for evaluating second language (L2) or foreign language (FL) learners’ grammatical ability – their proficiency in using grammar accurately and effectively across different contexts. This study aims to address this gap by investigating whether MC tests, which assess knowledge of grammar through the selection of correct answers from options, adequately reflect learners’ ability to use grammatical structures accurately, meaningfully, and appropriately. Data were collected from 68 English FL learners using two assessment tools: an MC task and a gap-filling task (GF task). Results indicate significant performance disparities between the MC and GF tasks, suggesting that MC tests may not consistently gauge learners’ true grammatical proficiency. This inconsistency underscores the limitations of MC testing as a singular measure of grammatical ability, particularly in assessing learners’ capacity to apply grammar meaningfully across diverse contexts. Further research is warranted to explore this issue comprehensively.